Predicting Adolescent Creativity from Openness to Experience and Intrinsic Motivation - Bennett, Laura; Moreau, Samuel; Matthews, Brian (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to investigate the predictive roles of openness to experience and intrinsic motivation in adolescent creativity. Methods and Materials: A correlational descriptive research design was employed, involving a sample of 380 high school students from Canada. Participants were selected using the Morgan and Krejcie sample size table through convenience sampling. Standardized instruments were used to assess the variables: the Torrance Tests of Creative Thinking (TTCT) for creativity, the Openness scale from the Big Five Inventory (BFI) for openness to experience, and the Intrinsic Motivation Inventory (IMI) for intrinsic motivation. Data analysis was performed using SPSS version 27. Pearson correlation coefficients were calculated to determine the strength and direction of the relationships between creativity and each predictor variable. A multiple linear regression analysis was then conducted to examine the combined predictive power of openness to experience and intrinsic motivation on creativity. Findings: Descriptive statistics revealed moderately high levels of creativity (M = 112.47, SD = 13.62), openness to experience (M = 36.28, SD = 4.81), and intrinsic motivation (M = 121.65, SD = 11.49). Pearson correlation analysis showed that creativity was significantly correlated with both openness to experience (r = .52, p < .01) and intrinsic motivation (r = .47, p < .01). Multiple linear regression analysis indicated that both predictors significantly contributed to creativity (R = .58, R² = .34, F(2, 377) = 72.96, p < .001), with openness to experience (β = .39, p < .001) and intrinsic motivation (β = .31, p < .001) emerging as significant predictors. Conclusion: The findings highlight that both openness to experience and intrinsic motivation play meaningful and complementary roles in predicting adolescent creativity. These results suggest that fostering openness and nurturing intrinsic motivation may be effective strategies for enhancing creative potential in educational settings.